Strategi Pemasaran Jasa Pendidikan Islam - Nikita Lusitania; Ahmad Zainuri; Nazarudin Nazarudin (Departement of Mathematics Education, 2024)
The paradigm in viewing education is gradually shifting. Initially, education was perceived and examined from a social aspect, but now society views education more as a corporate entity. The evolution of time requires Islamic educational institutions to prepare strategies, especially in terms of marketing their educational services. This article utilizes a literature review method, gathering relevant literature based on the topic discussed. It presents various strategies proposed by experts, ranging from Distinctive Competence, Advantage Competence, Focus, Communication, and Innovation, which are worth applying to sustain Islamic educational institutions. However, the foundation remains that marketing strategies for Islamic educational services must align with Islamic values and ethics, serve good educational purposes, uphold honesty, integrity, and educational quality as primary focuses. The existence of these strategies also faces impediments in implementation. The obstacles in marketing educational services are mostly temporary and stem from indications such as intense competition among existing schools, lack of innovation, insufficient management alignment, and frequently changing bureaucracy and regulations. This context necessitates prevention, where several forms of strategies can indicate a path leading to higher student interest, such as establishing clear and consistent regulations, enhancing educational quality, and continuous evaluation processes. With these preventive strategies and solutions, it is hoped that Islamic educational institutions will be better equipped in marketing their educational services